Assessment of Faecal Microbiota Transplant Stability in Deep-Freeze Conditions: A 12-Month Ex Vivo Viability Analysis - Soukupova, Hana; Rehorova, Veronika; Cibulkova, Ivana; Duska, Frantisek (Journal of clinical laboratory analysis, 2024)
BACKGROUND: Faecal microbiota transplantation (FMT) is an established treatment for Clostridioides difficile infection and is under investigation for other conditions. The availability of suitable donors and the logistics of fresh stool preparation present challenges, making frozen, biobanked stools an attractive alternative. AIMS: This study aimed to evaluate the long-term viability of bacterial populations in faecal samples stored at -80°C for up to 12 months, supporting the feasibility of using frozen grafts for FMT. METHODS: Fifteen faecal samples from nine healthy donors were processed, mixed with cryoprotectants and stored at -80°C. Samples were assessed at baseline and after 3, 6 and 12 months using quantitative culturing methods to determine the concentration of live bacteria. RESULTS: Quantitative analysis showed no significant decrease in bacterial viability over the 12-month period for both aerobic and anaerobic cultures (p = 0.09). At all timepoints, the coefficients of variability in colony-forming unit (CFU) counts were greater between samples (102 ± 21% and 100 ± 13% for aerobic and anaerobic cultures, respectively) than the variability between measurements of the same sample (30 ± 22% and 30 ± 19%). CONCLUSIONS: The study confirmed that faecal microbiota can be preserved with high viability in deep-freeze storage for up to a year, making allogenic FMT from biobanked samples a viable and safer option for patients. However, a multidonor approach may be beneficial to mitigate the risk of viability loss in any single donor sample.
Keywords: kryoprezervace; fekální transplantace; feces; zmrazování; Humans; Cryopreservation; bacterial viability; cryopreservation; mikrobiální viabilita; Freezing; long‐term stability; lidé; deep‐freeze storage; Microbial Viability; Feces; Male; Fecal Microbiota Transplantation; mužské pohlaví; faecal microbiota transplantation